Cationic Rhodium(I)‐Catalyzed Asymmetric Cyclohydroformylation of 1, 6‐Enynes with Formaldehyde. Issue 5 (24th January 2023) - Hayashi, Erin; Akiyama, Naoto; Kakiuchi, Kiyomi; Kawai, Tsuyoshi; Morimoto, Tsumoru
Abstract: We report a rhodium(I)‐catalyzed asymmetric cyclohydroformylation reaction of 1, 6‐enynes with formaldehyde. The reaction of 1, 6‐enynes with formaldehyde in the presence of a cationic Rh(I) catalyst, such as [Rh(cod)2 ] + OTf −, and a chiral biaryl diphosphine led to asymmetric cyclohydroformylation to produce aldehydes with higher‐order structures highly enantioselectively. This transformation procedure is applicable to a variety of enynes, with wide compatibility in various atoms liking between the alkyne and alkene parts, substituents at the alkyne terminus, and substituents at the alkene part, being converted to newly formed aldehydes in 14% to 90% yields with 50% to 98% ee . The products were further transformed with various nucleophiles to alcohols, an amine, and a diene without loss of chirality at their γ‐position. Abstract : The reaction of 1, 6‐enynes with formaldehyde in the presence of a cationic Rh(I) catalyst, such as [Rh(cod)2 ] + OTf −, and a chiral biaryl diphosphine led to asymmetric cyclohydroformylation to produce aldehydes with higher‐order structures highly enantioselectively.